A study of English The farewell expressions image schema from cognitive perspective - Ahmed Mohamed Fahid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This paper seeks to demonstrate how Johnson's theory influences farewell expressions images. Analyzing farewell expression English daily conversation, thus. Referring to new reading to the image of farewell expression that could form in different kinds of image schema like COTAINER, FORCE, PATH and LINKED. The results showed image scheme in English farewell expressions from everyday talks. These Expressions used to send someone farewell are closely related to the nature of English talks and human behavior. These statements demonstrated the generosity of people. The researcher concluded various image schemes are used in these farewell expressions, such as CONTAINTOR, which stands for TIME container. The IN-OUT orienting period is essential to this framework. Image Path A parting statement usually includes an origin or a SOURCE, an objective or a destination. The FORCE schema has multiple elements,